2022
DOI: 10.1186/s13054-022-04274-9
|View full text |Cite
|
Sign up to set email alerts
|

Score-based prediction model for severe vitamin D deficiency in patients with critical illness: development and validation

Abstract: Background Severe vitamin D deficiency (SVDD) dramatically increases the risks of mortality, infections, and many other diseases. Studies have reported higher prevalence of vitamin D deficiency in patients with critical illness than general population. This multicenter retrospective cohort study develops and validates a score-based model for predicting SVDD in patients with critical illness. Methods A total of 662 patients with critical illness wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…Os métodos estáticos buscam avaliar o estado volêmico por medidas indiretas da pré-carga cardíaca. Contudo, esses métodos de avaliação não conseguem predizer com confiança a responsividade ao volume, devido ao fato que a complacência cardíaca poder variar com as patologias de cada paciente e com o estado de choque circulatório [5,6]. Além disso, outro fator que prejudica a confiabilidade dos métodos estáticos se deve à dependência e influência das pressões pleurais sob o coração, sendo um fator de confusão da análise [5,6].…”
Section: Métodos De Avaliação De Fluido Responsividadeunclassified
See 1 more Smart Citation
“…Os métodos estáticos buscam avaliar o estado volêmico por medidas indiretas da pré-carga cardíaca. Contudo, esses métodos de avaliação não conseguem predizer com confiança a responsividade ao volume, devido ao fato que a complacência cardíaca poder variar com as patologias de cada paciente e com o estado de choque circulatório [5,6]. Além disso, outro fator que prejudica a confiabilidade dos métodos estáticos se deve à dependência e influência das pressões pleurais sob o coração, sendo um fator de confusão da análise [5,6].…”
Section: Métodos De Avaliação De Fluido Responsividadeunclassified
“…Sendo assim, o uso de fluidos intravenosos para melhorar a oferta de O2 para os tecidos deve ser realizada com cautela, pois estes fluidos são medicamentos e o seu uso de forma desorientada pode piorar o desfecho clínico. Estudos recentes têm demonstrado aumento na mortalidade, insuficiência renal aguda (IRA) e outra complicações relacionadas ao uso inadequado de fluidos em pacientes graves [4,5].…”
Section: Introductionunclassified
“…Many observational studies emphasize the association between 25(OH)D levels and cardiovascular disease, atherosclerosis, hypertension and heart disease in CKD patients and the elderly [ 145 ]. Vitamin D deficiency was an independent predictor of mortality in patients with or without heart failure [ 146 , 147 , 148 , 149 ]. It was suggested that seasonal fluctuations in mortality (i.e., decreased CVD-related deaths in the summer and increased deaths in the winter) might be related to the lower vitamin D levels in the blood during winter [ 150 ].…”
Section: Vitamin D Aging and Ckdmentioning
confidence: 99%